Glycine decreases desensitization of N-methyl-D-aspartate (NMDA) receptors expressed in Xenopus oocytes and is required for NMDA responses. - Lerma, J (1990)
In Xenopus oocytes injected with rat brain mRNA, as in neurons, glycine greatly potentiated responses of the N-methyl-D-aspartate (NMDA) type of excitatory amino acid receptor. Injected oocytes generated a partially desensitizing inward current in response to NMDA with 30 nM added glycine. As the added glycine concentration was increased from 30 nM to 1 microM, the NMDA response was increased and exhibited less desensitization. The relationship between the NMDA peak response and added glycine concentration indicated a single component response with apparent affinity of 0.29 microM and a Hill coefficient of 0.77. The desensitized response was also fit by the Hill relation with a lower affinity but similar coefficient. The time course of desensitization at 500 microM NMDA was exponential with a time constant (350 msec) that was independent of glycine concentration between 0.03 and 0.3 microM. At higher glycine concentration a slower component of decay (tau = 1.4 sec) was observed. This component was enhanced by increasing the extracellular Ca2+. NMDA without added glycine evoked a small transient response. However this response was suppressed completely by prewashing with the glycine antagonist 7-chlorokynurenic acid, suggesting that it may have been due to glycine contamination. The dose-response relation for low concentrations of glycine indicated that the measured level of glycine contamination accounted for these responses. These results indicate that glycine has at least two actions at the NMDA receptor: it enables channel opening by the agonist and decreases desensitization.